Kepemimpinan Kepala Sekolah Dalam Perencanaan Berbasis Data Melalui Rapor Pendidikan Guna Mewujudkan Sekolah Berkualitas Di Lembaga PAUD - Anwar, Rosyida Nurul; Aulia Maharani Dasilva (Jurnal Kajian Anak (J-Sanak), 2025)
Early Childhood Education (PAUD) is an essential stage in building the foundation of child development. Principals must be innovators who can develop new ideas to improve the quality of education. Implementing Data-Based Planning (PBD) is one strategy to improve the quality of PAUD education services. An objective picture of the quality of PAUD services needs to be analyzed based on factual data through system tools and education reports. This study explores the principal's leadership in optimizing data-based planning through education reports to realize quality schools in PAUD institutions. The method uses a qualitative approach with a case study type. The location of the research was in Bantengan Village Kindergarten 01, Madiun Regency, with the research subjects being the principal. Data were collected through observation, interviews, and analysis of documents related to the Education Report. The study showed that the principal optimized data-based planning through education reports using the Self-Evaluation Sheet and the Learning Environment Survey (Sulingjar). The Self-Evaluation Sheet was carried out by identifying and reflecting on priority indicators to formulate root problems and inspiration for improvement. The Learning Environment Survey was used to identify learning conditions, facilities and infrastructure, and partnerships with parents. These findings underscore the importance of accurate data in supporting ongoing reflection, planning, and evaluation processes in PAUD institutions.